2009
DOI: 10.1007/s00381-009-0979-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications of neuroblastic tumors: experience of a single center

Abstract: The prevalence rates of Horner's syndrome, OMA, CNS metastasis, and SCC were found to be 3.6%, 1.8%, 2.2%, and 9.4%, respectively. Metastasis to the CNS indicated a very poor prognosis. No differences in neurological improvement in patients with SCC were found between those treated with radiotherapy, laminectomy, or chemotherapy alone, but laminectomy and radiotherapy caused significant late sequelae. Early diagnosis and proper management is critical to avoid long-term sequelae in patients with SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 27 publications
1
44
2
3
Order By: Relevance
“…The grade of residual motor impairment after initial neurosurgery was lower but the difference was not statistically significant. Other studies have also reported no difference between either intervention 10–12 . It is of interest that, unlike another study that found that neurosurgery more often leads to scoliosis, 11 we found no difference in levels of scoliosis after either first‐line neurosurgery or chemotherapy.…”
Section: Discussioncontrasting
confidence: 63%
“…The grade of residual motor impairment after initial neurosurgery was lower but the difference was not statistically significant. Other studies have also reported no difference between either intervention 10–12 . It is of interest that, unlike another study that found that neurosurgery more often leads to scoliosis, 11 we found no difference in levels of scoliosis after either first‐line neurosurgery or chemotherapy.…”
Section: Discussioncontrasting
confidence: 63%
“…To determine the outcome of this asymptomatic patient group is not straightforward, since it is often not assessed and/or reported . In three studies, it is explicitly mentioned that the asymptomatic patients do not have any long‐term health problems.…”
Section: Resultsmentioning
confidence: 99%
“…8,46,50 Two studies found a lower rate of disseminated disease compared to NBL patients without spinal cord compression. 46,50 Six studies found an overall survival (OS) benefit for NBL patients with intraspinal extension compared to patients without spinal involvement, 8,37,46,[49][50][51] the difference being significant in only two studies. 46,50 An improved event-free survival (EFS) was reported in four studies, 8,44,50,51 the difference being significant in only one study.…”
Section: Characteristics Of Nbl With Intraspinal Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroblastomas are the most common extracranial solid tumors in children, accounting for about 8%-10% of all pediatric tumors (20,21). That said, there are no reports of HSP associated with a neuroblastoma or other malignancy in children.…”
Section: Discussionmentioning
confidence: 99%